SISTEM TELEMETRI PEMANTAU GAS KARBON DIOKSIDA (CO2) MENGGUNAKAN JARINGAN WIFI - Muhammad Izzuddin Shofar; Suryono Suryono (Youngster Physics Journal, 2014)
This research has developed telemetry system for CO2 gas monitoring using MG811 gas sensor with Wifi network system. Telemetry sistem is very important because CO2 is lethal gas for human. This system allows for monitoring, data acquisition and early warning from somewhere far away from the gas source. This data acquisition system using MG811 gas sensor, ATmega8535 microcontroller and I2C communication protocol for data transfer between sensor and microcontroller. Data from microcontroller is sent to Wiz6000 using serial communication protocol. Wiz6000 is a serial to wifi module. Data from wiz6000 then read by computer that connected to Wifi network belong to wiz6000 with IP and port that suited with the configuration.CO2 gas sensor is being realized with reading the sensor value via I2C communication protocol with MG811 and ATmega8535 miconcontroller. After calibration, the linier coefficeient R = 0,997 toward standar CO2 meter. Data acquisition CO2 concentration with MG811 is sent via telemetry system using Wifi network that can be accessed using computer program. The program then will show the data real-time and showed in a table, chart and save them to MySQL database. This telemetry monitoring sistem also a early warning system that give a warning when the CO2 concentration increased above the safety standard.Keyword: CO2, hazardous gases, sensor, data acquisition, telemetry